An Intricate Investigation of Ethnobotanical Practices Concerning the Utilization of Medicinal Flora for Addressing Reproductive Health Disorders within the Dubri Wildlife Sanctuary Located in the Sidhi District of Madhya Pradesh, India - Mohammad Salim; Pradeep Kumar Dwivedi; Mohammad Shahid Masroor (Recent Trends in the Study of Botanical Research Volume - 1, 2023)
The ethnobotanical investigations pertaining to a specific geographical area involve an intricate and laborious process. In this context, a research paper has meticulously documented the indigenous wisdom concerning the utilization of medicinal plants for addressing various reproductive health disorders and ailments. The locale under study is the Dubri Wild Life Sanctuary situated in the Sidhi District of Madhya Pradesh, India. The conducted survey employed a meticulous approach that encompassed direct and probing inquiries directed towards traditional healthcare practitioners, community leaders, and individuals with educational backgrounds. The crux of the study centers around a comprehensive analysis of 22 distinct plant species, each attributed to the management of 11 discrete reproductive disorders. These ailments encompass a range of conditions including leucorrhea, excessive uterine bleeding, infertility in both males and females, nocturnal emissions, involuntary seminal emissions, pregnancy-induced vomiting, gonorrhea, complications during childbirth, augmentation of lactation, irregular menstrual cycles, and female contraception. The identified medicinal plants are expounded upon through their botanical and indigenous nomenclature, affiliated botanical families, specific plant parts that are utilized, the time-honored techniques employed in the preparation of therapeutic remedies, recommended dosages, and the manner in which these formulations are administered to human subjects.